Are proton symports in yeast directly linked to H(+)-ATPase acidification? - Kotyk, A; Dvoráková, M (Biochimica et biophysica acta, 1992)
Transport of amino acids in Saccharomyces cerevisiae is an H(+)-driven secondary active transport. Inhibitors of the plasma membrane H(+)-ATPase, particularly heavy water, diethylstilbestrol and suloctidil, were shown to affect the H(+)-extruding ATPase activity as well as the ATP-hydrolyzing activity, to a similar degree as they inhibited the transport of amino acids. The inhibitors had virtually no effect on the membrane electric potential or on the delta pH which constitute the thermodynamically relevant source of energy for these transports. Transport of acidic amino acids was affected much more than that of the neutral and especially of the basic ones. The effects were greater with higher amino acid concentrations. All this is taken as evidence that the amino acid carriers respond kinetically to the presence of protons directly at the membrane site where they are extruded by the H(+)-ATPase, rather than to the overall protonmotive force.
Keywords: deuterium; Lysine; protony; lysin; membránové potenciály; glutamáty; Glutamates; Hydrogen-Ion Concentration; Proton-Translocating ATPases; Deuterium; diethylstilbestrol; Saccharomyces cerevisiae; protonové ATPasy; Suloctidil; Diethylstilbestrol; Leucine; kyselina glutamová; leucin; Protons; koncentrace vodíkových iontů; Glutamic Acid; suloktidil; Membrane Potentials